JENIS PRODUK DAN POLA AGROFORESTRI DI DESA SOSOR DOLOK, KECAMATAN HARIAN, KABUPATEN SAMOSIR - Irvan Efendi Naibaho; Siti Latifah; Tri Martial (Program studi Kehutanan USU, 2015)
Agroforestry is closely related to the optimization of the use of land to provide for the life of farmers in order to conserve natural resources.One important part in the management of agroforestry that is the type of plant and the pattern applied on agricultural land. The experiment was conducted in the village of Sosor Dolok, District Harian, Samosir regency of June-July 2014. The collection of data obtained from the field observations through interviews and questionnaires were analyzed descriptively and qualitatively. types of agroforestry products in the village there Dolok bill 20 species with most types of coffee plants, namely the number of beneficiaries by 25 respondents. Agroforestry pattern applied in the village Sosor Dolok there are 2 types of pattern, agrisilvikultur with 15 farmers who implementing and patterns agrosilvopastura by 5 farmers.Keywords: Agroforestry, Forest Product, Land Management Patterns